A study on assessment of knowledge on biomedical waste management among health care workers of Malabar Medical College Teaching Hospital, Calicut, Kerala, India - K. R., Ananthachari; C. V., Divya (International Journal Of Community Medicine And Public Health, 2016)
Background: Health care institutions and hospitals generate biomedical waste which can introduce various infections and injuries to the healthcare workers, patients and harm the surrounding environment. For proper management of biomedical waste Government of India has introduced the biomedical waste management and Handling rules in 1998, unfortunately health care workers awareness regarding biomedical waste segregation, handling and management is minimal hence, the study addresses the issues related to it. Methods: This cross sectional study was conducted in the month of July 2016 among health care workers at Malabar Medical College Hospital and Research Centre, Calicut, India. A pre-tested, semi-structured questionnaire was used to elicit the various information like collection, segregation and disposal of biomedical waste. Results: 567 health care workers were interviewed.44.3% (251) opined correctly that biomedical waste should not be kept more than 48 hours at hospital settings. 61.6% (349) opined waste sharps should be disposed in white/blue puncture proof containers.89.6% (508) knew about HIV, hepatitis B and hepatitis C are common infections transmitted due to improper biomedical waste management. 60.5% (345) and 61% (346) opined that human anatomical waste and pads, cottons, dressings should be disposed in yellow bags, respectively. 70.7% (401) were fully immunised against hepatitis B. 29.8% (169) had received training on biomedical waste management. Conclusions: Knowledge regarding biomedical waste disposal among nursing staff is satisfactory compared to other health care workers, adequate training among health care workers can improve the biomedical waste management and handling practices at hospital settings.